Constructing Images of the Divine: Latent Heterogeneity in Americans' Impressions of God - Davis, Nicholas T. (Journal for the scientific study of religion, 2019)
How do individuals psychologically organize their images of the divine? Most work on this topic is factor-analytic in nature, finding that God images vary with respect to love, judgment, and engagement. However, few studies look at how individuals spontaneously combine these divine dimensions into composite images of God. To fill this gap, we subject data from the 2010 Baylor Religion Survey to latent class analysis and find evidence for five depictions of God: (1) a poorly defined, uninvolved deity; (2) a loving, nonjudgmental deity who is engaged with humanity; (3) a nullity or nonentity; (4) a loving deity who is neither judgmental nor engaged with humanity; and (5) a loving deity who is also both judgmental and engaged. We then present evidence that individuals holding these images vary in their denominational background, religious attitudes and behaviors, and general traits. Our findings suggest that individuals may impose not only a dimensional structure on images of the divine, but a categorical one as well.